Wall Movement Monitoring Using High-Resolution Target Movement Monitoring System - D. Apel; R. Moss; S. Watkins; B. Gray (Society for Mining, Metallurgy & Exploration, 2007)
Currently, there are several techniques and technologies available which are used by mining industry in its attempts to remotely monitor the ground movements both at surface and underground mines. The currently available remote distance meters and distance change monitors mainly use phase change and time-of-flight techniques. The described monitor uses triangulation technique to track position of an optical spot projection and then image processing to measure mine wall movements. The system can be easily automated and poses no obstruction to mine traffic. The position of an off-normal laser spot will shift as the target wall moves. The described ground movement monitoring system has potential for superior accuracy and target monitoring can be made through air (gaseous) or other transparent media. The theoretical accuracy and range of this system depends solely on the resolution and focal length of the camera being used. The remote capabilities of the system make it uniquely suited to applications where monitoring is required in high-traffic, inaccessible, or unstable and dangerous areas of a mine.